The Main Casual Factors Associated with The Incidence of Asphyxia Neonatorum - Anisa Ulfah; Defrin Defrin; Ulfa Farrah Lisa; Firdawati Firdawati; Erda Mutiara Halida (Women, Midwives and Midwifery, 2023)
Background: Asphyxia is the second most common cause of neonatal death after babies with low birth weight (LBW). The factors that can cause asphyxia include preeclampsia, premature birth, prenatal anemia, antepartum bleeding and premature rupture of membranes. Purpose: This study aimed to determine the main causative factors associated with the incidence of asphyxia neonatorum at RSUP Dr. M. Djamil Padang in 2021. Methods: This research was a quantitative research with an analytic approach with a cross sectional design, was conducted in the Medical Record Sub-Division of RSUP Dr. M. Djamil Padang in December 2022. The sample in this study were babies who were diagnosed with asphyxia totaling 132 people obtained by total sampling technique. Collection data were taken from patient medical records and analyzed univariately, bivariately (test chi square), and multivariate (logistic regression analysis) with 95% CI. Results: The result showed that 77.3% of patients had moderate asphyxia. The result of this study showed that majority of patients with severe asphyxia with preeclampsia mothers 60.0% (p=0.001), premature birth 76,7% (p=0.044), anemia mothers 53,3% (p=0.035), did not experience antepartum hemorrhage 83,3% (p=0.390), and premature rupture of membranes 73,3% (p=0.000). The most dominant factor was premature rupture of membranes with OR=34.988). Conclusion: It was concluded that there was a relationship between preeclampsia, premature birth, prenatal anemia, premature rupture of membranes, and there was no relationship between antepartum bleeding and neonatal asphyxia. The factor that has the most dominant influence on the incidence of neonatal asphyxia is premature rupture of membranes. Suggestions for health workers to maintain and improve services to patients, especially asphyxia neonatorum.